2006
DOI: 10.1029/2006gl027938
|View full text |Cite
|
Sign up to set email alerts
|

Temporal change in site response caused by earthquake strong motion as revealed from coda spectral ratio measurement

Abstract: The spectral ratios of coda waves of local earthquakes have been often used as measures of relative amplification factors of different sites. Applying this method to coda waves registered by seismometers installed on the surface and at the bottom of a borehole, we succeeded in stably measuring the temporal change in site response associated with the occurrence of a large earthquake strong motion. A remarkable drop of coda spectral ratio and a shift of the peak frequency were observed during strong shake at two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
80
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 14 publications
10
80
0
1
Order By: Relevance
“…The sharp reductions of the peak frequency and peak spectral ratio followed by gradual recovery observed in this study (Fig. 3) are similar to the previous observations of nonlinear site response using spectral ratio approaches (e.g., Sawazaki et al, 2006;Wu et al, 2009a). Hence, we attribute the temporal changes of the spectral ratios to nonlinear site response during the main shock.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The sharp reductions of the peak frequency and peak spectral ratio followed by gradual recovery observed in this study (Fig. 3) are similar to the previous observations of nonlinear site response using spectral ratio approaches (e.g., Sawazaki et al, 2006;Wu et al, 2009a). Hence, we attribute the temporal changes of the spectral ratios to nonlinear site response during the main shock.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have found clear evidences of soil nonlinearity after previous large earthquakes in Japan, including the 1995 M w 6.8 Kobe earthquake, 2000 M w 6.8 Western Tottori earthquake, 2003 M w 8.3 Tokachi-Oki earthquake, 2003 M w 7.0 Miyaki-Oki earthquake, and 2004 M w 6.6 Niigata earthquake (e.g., Pavlenko and Irikura 2002;Sawazaki et al, 2006;Rubinstein et al, 2007;Assimaki et al, 2008;Wu et al, 2009aWu et al, , 2010. The sharp reductions of the peak frequency and peak spectral ratio followed by gradual recovery observed in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Passive image interferometry (PII) uses this concept in detecting changes through the monitoring of auto-and/or cross-correlation of daily ambient noise (Sens-Schönfelder and Wegler, 2006;Wegler and Sens-Schönfelder, 2007), with successful applications to coseismic changes (Ohmi et al, 2008;Brenguier et al, 2008a;Wegler et al, 2009) and changes associated with volcanic eruptions (Brenguier et al, 2008b). There are two physical mechanisms that may explain postseismic changes in velocity; one is a relaxation of fault zone damage by healing (Vidale and Li, 2003); the other is a nonlinear change in very shallow subsurface regions caused by the incidence of strong motion (Sawazaki et al, 2006). For velocity changes associated with large earthquakes, it is quite difcult to distinguish which mechanism is responsible.…”
Section: Introductionmentioning
confidence: 99%